Evaluation of the use of milk urea nitrogen (MUN) as an indicator of nutritional status of dairy cattle in smallholder farms in Kiambu district - Wambugu, M.; Wahome, R.G.; Gachuiri, C.; Tanner, J.C.; Kaitho, R. (International Livestock Research Institute, 1998)
A survey was conducted to evaluate the use of Milk Urea Nitrogen as an indicator of nutrition status of lactating animals. Twenty-seven animals in a randomly selected sample of 21 farms in Kiambu District were monitored for nutritional status for 12 weeks. Fortnightly records were taken on feed offered, body condition, body weight and milk yield. Milk samples were collected weekly and analysed for MUN. Preliminary results indicated that there was a significant (P<0.05) negative correlation between MUN and milk yield, and a marginal correlation between MUN and body weight. There was no significant relationship between MUN and Body condition score. The data so far collected, which excludes the feed data indicate that MUN, may to an extent be a reliable indicator, of nutritional status of dairy cattle under smallholder farm conditions.